Chinese Iconography Thesaurus - Victoria and Albert Museum (2019)
Traditionally considered a methodology rooted in European art history, iconography has been historically employed to index and access images related to Euro-American art. Because of the lack of alternative models for documenting non-western artefacts, Chinese art objects housed in European and North American collections have often been catalogued according to Eurocentric classifications. The CIT presents a unique opportunity to create an alternative classification scheme rooted in the specificity of Chinese visual culture and foster systematic comparison between Chinese and European art.